S-Matrix and Feynman Space-Time Diagrams to Quantum Brain Approach An Extended Proposal - BAŞAR, EROL (Anka Publisher, 116-11 Sok No.10 K 2 D 2, Bornova, Izmir 35050, Turkey, 2009)
This report describes the importance of oscillations in brain function and introduces metaphors to quantum dynamics. In order to analyze scattering processes at the level of elementary particles Werner Heisenberg proposed the use of the so-called S-Matrix to understand nuclear interactions by studying ingoing at outgoing particles. Later, Richard Feynman developed useful schemes in order to visualize processes of elementary particle interactions. In the present report a metaphor to Feynman Diagrams is developed in order to model the "Ongoing Brain Activity and Event Related Oscillations". The response susceptibility of the brain shows a probabilistic causality similar to uncertain processes in elementary particle physics. A new grammar called Brain Feynman Diagrams is proposed in order to show brain oscillatory responses as a more visible construct in comparison to conventional compound brain potentials.
Keywords: brain; brain oscillations; quantum brain; Feynman diagrams; s-matrix; neurocognitive networks; 3-year-old children; evoked potentials; human-memory; oscillations; theta; responses; dynamics; alpha; beyin; beyin salınımlar; kuantum beyin; Feynman diyagramları; bilişsel ağlar; 3 yaşındaki çocuk; uyarılmış potansiyeller; İnsan bellek; salınımlar; teta; tepkiler; dinamik; alfa